Autonomy & accountability in 4IR: Ethical implications of AI driven automation in Sustainable Business - Moutusi Tanha; Sohel Parvez; Kabbya Das Papon; Md. Erfanul Hoque; Muhammad Al Amin; Shatirtho Sarkar; Sultan Mahmud; Md Zakir Hossain (Global Academy of Multidisciplinary Studies, 2025)
Purpose: The purpose of this study is to explore how AI in Industry 4.0 is impacting work and business, posing ethical concerns. It addresses labor market disruptions, organizational transformation, sustainability, algorithmic bias, data privacy, and job displacement ethics. The report examines how AI adoption might help inclusive economic development and SDGs. Research Methodology: The research uses mixed methodologies, incorporating qualitative and quantitative data. Secondary sources include 2019–2025 academic journal articles, government papers, industrial publications, and international databases. The research uses a systematic literature review, thematic analysis, statistical evidence from robotics adoption databases, and case studies in manufacturing, logistics, and service industries to discover patterns. The integration of theory and practice employs descriptive-exploratory approaches. Results: Results indicate rising global use of industrial robots and AI, with South Korea, Singapore, and Germany exhibiting the highest robot density. AI automates monotonous activities and creates hybrid professions that demand digital and analytical talents. AI-adopting companies are becoming more flexible and data-driven. However, ethical issues such algorithmic bias in recruiting and decision-making, surveillance technology privacy threats, and low-skilled worker job displacement persist. Conclusions: AI has promise to improve productivity, efficiency, and sustainability, but requires strong governance, ethical frameworks, and ongoing reskilling. Without controls, inequities and ethical problems may grow Limitations: The study depends on secondary data and literature evaluation, with minimal original field research for context-specific insights. Contribution: This study advances ethics, management, sustainability, and offers practical AI recommendations for stakeholders.